2012
DOI: 10.1080/00981389.2012.692351
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Caregiving, Satisfaction of Life, and Social Repercussions Among Family Caregivers, Two Years Post-Stroke

Abstract: Cerebrovascular diseases are a public health and social policy priority in Europe due to their high prevalence and the long-term disability they may result in (as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Education programs for caregiver and stroke participant should include supportive problem solving and skill development, 860 "how to's" of physical care needs and financial assistance, 861 medications, 862 respite, domestic assistance, and reassurance. 863 Ongoing support for the caregiver favorably affects the stroke survivor and caregiver. This support comes in many different actions.…”
Section: Winstein Et Al Guidelines For Adult Stroke Rehabilitation Anmentioning
confidence: 99%
“…Education programs for caregiver and stroke participant should include supportive problem solving and skill development, 860 "how to's" of physical care needs and financial assistance, 861 medications, 862 respite, domestic assistance, and reassurance. 863 Ongoing support for the caregiver favorably affects the stroke survivor and caregiver. This support comes in many different actions.…”
Section: Winstein Et Al Guidelines For Adult Stroke Rehabilitation Anmentioning
confidence: 99%
“…These activities may improve ability to make relevant choices to promote better health. It may also help to avoid resentment and promote psychological strength and confidence in the future [40]. The fact that the LS was higher in female than in male patients calls for further research on severity, symptoms and potential risk factors such as health-related behaviours, nutrition, leisure, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has shown that decreased psychological QOL in caregivers is correlated with the number of hours spent in caregiving. That is because an increased level of involvement or the number of hours spent in caregiving often results in lower participation in social activities, as well as increased frustration and depression (Lurbe-Puerto et al 2012).…”
Section: New Situation Mediation Poststrokementioning
confidence: 99%
“…That is because an increased level of involvement or the number of hours spent in caregiving often results in lower participation in social activities, as well as increased frustration and depression (Lurbe‐Puerto et al . ).…”
Section: Introductionmentioning
confidence: 97%